Money, interest rates, and inflation - Mishkin, Frederic S. (Economists of the twentieth century, 1993)
Frederic Mishkin's work has been dedicated to understanding the relationship between money, interest rates and inflation, an integral part of the monetary transmission process. The 15 essays in this collection - unabashedly empirical and rigorous - include much of Professor Mishkin's most frequently cited work. Money, Interest Rates and Inflation offers a coherent and informative assessment of how monetary policy affects the economy. In addition, the essays in this collection illustrate how rational expectations econometrics can be used in empirical research on a broad range of topics and issues. The introductory essay provides an overview of Professor Mishkin's work and the unifying themes which have influenced his thought. The book will be of interest to researchers and graduate students in the areas of econometrics, finance and monetary-macroeconomics